Optimalisasi Google SEO Menggunakan Google MyBusiness Untuk Memasarkan Produk Asuransi (Studi Kasus Kantor Galaxy Lion Heart) - Fitri Astutik; Muhammad Rizkillah (Bakti Sekawan : Jurnal Pengabdian Masyarakat, 2022)
The FC (Financial Consulting) Galaxy Lion Heart Lombok team conducts marketing of financial services (insurance) products only limited to social media such as on Facebook, Instagram, Twitter and WhatsApps groups. Their activities are only limited to sharing product flyers, sometimes the presence of FC activities is not necessarily liked by the community on social media. Therefore, to maximize the potential of digital marketing in the FC profession at the Lombok branch office, namely Galaxy Lion Heart, a mentoring activity was made to use Google SEO for the FC profession in increasing sales on financial services products of PT AJ Generali Indonesia. This Community Service (PkM) is part of a routine assignment every semester once a year which has been given routine tasks to resource persons by the highest leadership of the Lombok branch office, the name of the branch office is Galaxy Lion Heart Lombok. The method of this PkM activity is to assist in creating links with Google SEO to each FC team in the office. The Pk Mini implementation chart describes the following: a) Conducting a literature study; b) Determination of the type of assistance; d) Activity planning; e) Composing the topic of presentation and practice materials; f) Delivery of material topics; g) Demonstration of Google SEO material topics; h) Discussion of Google SEO materials; i) Creation of PkM reports; j) Creation of PkM articles; k) Publication of the PkM journal. The results of this PkM output are in the form of PkM journal publications and a practicum module for making Google SEO for Financial Consulting. This activity is highly appreciated by most of the FC teams, therefore their attendance every semester increases in the class. Therefore, this PkM activity has been requested directly by the head of the Galaxy Lion Heart office to be held every year.